Zanes Speak: Olympic Fines in Hellenic Intellectual and Political Context - Buraselis, Kostas (Hyperboreus, 2017)
Olympic Zanes, statues erected with the ﬁnes of athletic transgressions, apparently not further signiﬁcant data of economic administration, are shown to be more deeply connected with and able to contribute to the understanding of the moral values, the self-image and the political life of ancient Greek society, in the ﬁrst period of Macedonian control over the Greek cities.